Structural and electronic properties of zinc blende B xAl 1-xN yP 1-y quaternary alloys via rst-principle calculations - Abdiche, A. (Elsevier B.V., 2012)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home